Perceived usefulness technology at public university in central Mexico - García Lirios, Cruz; E Crespo, Julio (Journal of Social Review and Development, 2023)
Objective of this study was to carry out a systematic review of the literature to reveal the policies of metropolitan mobility and peri-urban health, focusing the discussion on the effects of public transport safety on the health of users. Methodology: A documentary, retrospective and meta-analytic study was carried out with a non-probabilistic selection of indexed sources published from 2020 to 2023 and search with the key words. Results: Prevalence of data that sustain the non-exposure to risk events derived from mobility policies in public transport safety and the health of users. Discussion: Political comparisons reveal the prevention of the effects of risk events on the health of users. Conclusion: Mobility policies, focused on the effects of transport safety on the health of users, do not recognize the risks of exposure or the short, medium and long-term consequences.